Discovery of 1, 3-dihydro-2, 1, 3-benzothiadiazole 2, 2-dioxide analogs as new RORC modulators. Issue 9 (1st May 2015) - Muegge, Ingo; Collin, Delphine; Cook, Brian; Hill-Drzewi, Melissa; Horan, Josh; Kugler, Stanley; Labadia, Mark; Li, Xiang; Smith, Lana; Zhang, Yunlong
Graphical abstract: Abstract: Structure-based and pharmacophore-based virtual screening in combination with combinatorial chemistry and X-ray crystallography led to the discovery of a new class of benzothiadiazole dioxide analogs with functional activity as RORC inverse agonists. The early RORC SAR compound 14 exhibited RORC inhibition in a cell based reporter gene assay of 5.7 μM and bound to RORC with an affinity of 1.6 μM in a fluorescence polarization assay displacing a ligand binding site probe. Crystallography confirmed the binding mode of the compound in the ligand binding domain displaying the engagement of a novel sub pocket close to Ser404. Subsequent optimization yielded compounds with enhanced RORC inverse agonist activity. The most active compound 19 showed an IC50 of 440 nM in a human PBMC assay.